Metody wielowymiarowego skalowania obiektów symbolicznych - Pełka, Marcin (Methods of Multidimensional Scaling for Symbolic Objects, 2007)
The aim of this article is to present one of symbolic clustering methods, the INTERSCAL method with problems, which will be encountered while applying this method. Article compares also this method with another multidimensional scaling method for symbolic objects (SYMSCAL). The article will compare in the empirical part the symbolic multidimensional scaling results based on LCD monitors market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 178-185